2021
DOI: 10.1021/acsami.1c20419
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Superhydrophobic Composites with Thermostability, UV Resistance, and Coating Transparency

Abstract: Despite the market demand for biofiber assemblies endowed with superhydrophobicity being huge, the current approaches to their production are complicated, time-consuming, and even pose a serious threat to the environment. Here, we report a simple surface treatment strategy to prepare environmentally friendly superhydrophobic biofiber composites. The obtained samples have certain UV resistance properties, which are mainly determined by the titanium dioxide (TiO2) dosage. Additionally, the sample has excellent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…WCA of the MCNF films and TOCN films increased from 55.6° to 76.2° and from 56.4° to 68.7°, respectively, which demonstrated the increase in surface hydrophobicity of films. The increases in contact angles were due to talc platelets changing the surface structure, resulting in increased surface roughness . In addition, the water swelling ratio and water solubility of CNF films were characterized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WCA of the MCNF films and TOCN films increased from 55.6° to 76.2° and from 56.4° to 68.7°, respectively, which demonstrated the increase in surface hydrophobicity of films. The increases in contact angles were due to talc platelets changing the surface structure, resulting in increased surface roughness . In addition, the water swelling ratio and water solubility of CNF films were characterized.…”
Section: Resultsmentioning
confidence: 99%
“…The increases in contact angles were due to talc platelets changing the surface structure, resulting in increased surface roughness. 51 In addition, the water swelling ratio and water solubility of CNF films were characterized. The results showed that the stability in water of CNF films increased with the addition of talc platelets (Figure S3).…”
Section: ■ Introductionmentioning
confidence: 99%
“…As seen in Figure c, the mass per unit area considerably affects the hydrostatic pressure. These findings show that the adjustable porosity of the hydrophobic microfibrous structure of the PET/PA6 bicomponent microfilament textiles produced by coating them with a C 6 -based fluorocarbon polymer followed by thermal-belt bonding may significantly increase the hydrostatic pressure . Surprisingly, the PET/PA6 bicomponent microfilament textiles also showed very strong resistance to blood penetration (the anti-blood grades are given in Table S1).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The excellent thermal stability of cellulose-based fiber paper is crucial for accommodating diverse environmental requirements while maintaining its original properties under elevated temperatures. 33 Therefore, we characterized the thermal stability of CE paper and CP composite paper. Figure 10a,b shows the TGA and DTG curves of CE and CP composite paper.…”
Section: Thermal Stability and Thermoformability Of Cp Composite Papermentioning
confidence: 99%